Low Rate of Between-Population Seed Dispersal Restricts Genetic Connectivity and Metapopulation Dynamics in a Clonal Shrub - Merwin, L.; He, Tianhua; Lamont, Byron; Enright, Neal; Krauss, S. (Public Library of Science, 2012)
Clonal species normally have low seed production, low recruitment rates and long lifespans, and it is expected that the rates of long-distance dispersal (LDD) of seeds will be low as well. Banksia candolleana is a clonal shrub in Mediterranean-type, fire-prone sclerophyll shrublands of southwestern Australia, whose reproductive biology and population dynamics contrast with those of co-occurring nonclonal congeneric species, all of which are restricted to a mosaic of sand dunes set within a matrix of inhospitable swales. Using microsatellite markers, we genotyped 499 plants in all 15 populations of B. candolleana within a 12-km2 area, assessed population genetic differentiation, and quantified the effective rate of interpopulation seed dispersal through genetic assignment of individuals to populations. We measured life history, reproductive and demographic attributes, and compared these with two co-occurring Banksia species, a non-clonal resprouter and a nonsprouter. B. candolleana has much higher levels of population genetic differentiation, and one-third the rate of interpopulation seed migration, as the other two species (2.2% vs 5.5−6.8% of genotyped plants inferred to be immigrants), though distances reached by LDD are comparable (0.3−2.3 km). The low rate of interpopulation dispersal was supported by an analysis of the age structure of three populations that suggests a mean interdune migration rate of <800 m in 200 years, and 60% of suitable dunes remain uninhabited. Thus, B. candolleana has poor properties for promoting long-distance dispersal. It is unclear if these are idiosyncratic to this species or whether such properties are to be expected of clonal species in general where LDD is less critical for species survival.